Spatiotemporal segregation in visual search: evidence from parietal lesions. - Olivers, C; Humphreys, G (2004)
The mechanisms underlying segmentation and selection of visual stimuli over time were investigated in patients with posterior parietal damage. In a modified visual search task, a preview of old objects preceded search of a new set for a target while the old items remained. In Experiment 1, control participants ignored old and prioritized new items, but patients had severe difficulties finding the target (especially on the contralesional side). In Experiment 2, simplified displays yielded analogous results, ruling out search ease as a crucial factor in poor preview search. In Experiment 3, outlines around distractor groups (to aid segmentation) improved conjunction but not preview search, suggesting a specific deficit in spatiotemporal segmentation. Experiment 4 ruled out spatial disengagement problems as a factor. The data emphasize the role of spatiotemporal segmentation cues in preview search and the parietal lobe in the role of these cues to prioritize search of new stimuli.